COVID-19-related future anxiety is associated with the health-related quality of life in school-aged children and adolescents—A cross-sectional study - Kästner, Anika; Lücker, Petra; Hannich, Arne; Schmeyers, Lena; Lücker, Janny; Hoffmann, Wolfgang (Frontiers in Public Health, 2022)
Background: Over the course of the COVID-19 pandemic, previous studies have shown that the physical as well as the mental health of children and adolescents significantly deteriorated. Future anxiety caused by the COVID-19 pandemic and its associations with quality of life has not previously been examined in school children. Methods: As part of a cross-sectional web-based survey at schools in Mecklenburg-Western Pomerania, Germany, two years after the outbreak of the pandemic, school children were asked about COVID-19-related future anxiety using the German epidemic-related Dark Future Scale for children (eDFS-K). Health-related quality of life (HRQoL) was assessed using the self-reported KIDSCREEN-10. The eDFS-K was psychometrically analyzed (internal consistency and confirmatory factor analysis) and thereafter examined as a predictor of HRQoL in a general linear regression model. Results: A total of N=840 8-18-year-old children and adolescents were included in the analysis. The eDFS-K demonstrated adequate internal consistency reliability (Cronbach’s α=0.77), and the confirmatory factor analysis further supported the one-factor structure of the four-item scale with an acceptable model fit. Over 43% of students were found to have low HRQoL. In addition, 47% of the students sometimes or often reported COVID-19-related fears about the future. Children with COVID-19-related future anxiety had significantly lower HRQoL (B=-0.94, p<0.001). Other predictors of lower HRQoL were older age (B=-0.63, p<0.001), and female (B=-3.12, p<0.001) and diverse (B=-6.82, p<0.001) gender. Conclusion: Two years after the outbreak of the pandemic, school-aged children continue to exhibit low HRQoL, which is further exacerbated in the presence of COVID-19-related future anxiety. Intervention programs with an increased focus on mental health also addressing future anxiety should be provided.